Like a Virgil: Georgic Ontologies of Agrarian Work in Canadian Literature - Baker, Jennifer (Université d'Ottawa / University of Ottawa, 2019)
In this dissertation, I argue that two dominant perspectives on farming in Canada—the technoscientific capitalist perspective on modern industrial farming and the popular vision of hard-won survival on the family farm—both draw on narrative and aesthetic strategies that have deep roots in distinct, but related variations of the georgic tradition, which arrived in Canada in the eighteenth century and continues to shape literary representations and material practices today. Critics of Canadian literature have tended to subsume the georgic under the category of pastoral, but I argue that the georgic is a separate and more useful category for understanding the complex myths and realities of agricultural production in Canada precisely because it is a literary genre that focuses on the labour of farming and because it constitutes a complex and multi-generic discourse which both promotes and enables critique of dominant agricultural practices. I argue that, despite its sublimation beneath the pastoral, the georgic mode has also been an important cultural nexus in Canadian literature and culture, and that it constitutes a set of conventions that have become so commonplace in writing that deals with agricultural labour and its related issues in Canada that they have come to seem both inevitable and natural within the Canadian cultural tradition, even if they have not been explicitly named as georgic. By analyzing a variety of texts such as Oliver Goldmith’s The Rising Village, Isabella Valancy Crawford’s Malcolm’s Katie, Susanna Moodie’s Roughing It in the Bush, Frederick Philip Grove’s Settlers of the Marsh, Martha Ostenso’s Wild Geese, Al Purdy’s In Search of Owen Roblin, Robert Kroetsch’s “The Ledger,” Christian Bok’s Xenotext, Rita Wong’s Forage, and Phil Hall’s Amanuensis, I recontextualize Canadian writing that deals with agrarian work within two distinct but related georgic traditions. As Raymond Williams and others have shown, the georgic’s inclusion of both pastoralizing myths and material realities makes it useful for exploring ecological questions. The georgic is often understood in terms of what Karen O’Brien has called the imperial georgic mode, which involves a technocratic, imperialist, capitalist approach to agriculture, and which helped theorize and justify imperial expansion and the technological domination of nature. But as ecocritics like David Fairer, Margaret Ronda, and Kevin Goodman have argued, the georgic’s concern with the contingency and precariousness of human relationships with nonhuman systems also made it a productive site for imagining alternatives to imperial ways of organizing social and ecological relations. Ronda calls this more ecologically-focused and adaptable georgic the disenchanted georgic, but I call it the precarious georgic because of the way it enables engagement with what Anna Tsing calls precarity. Precarity, as Tsing explains, describes life without the promise of mastery or stability, which is a condition that leaves us in a state of being radically dependent on other beings for survival. “The challenge for thinking with precarity,” she writes, “is to understand the ways projects for making scalability have transformed landscape and society, while seeing also where scalability fails—and where nonscalable ecological and economic relations erupt” (42). By tracing the interplay between imperial and precarious georgic modes in Canadian texts that have mistakenly been read as pastoral—from Moodie’s settler georgic to the queer gothic georgic of Ostenso’s Wild Geese to the provisional and object-oriented georgics of Robert Kroetsch and Phil Hall—I argue that the precarious georgic strain has always engaged in this process of thinking with precarity, and that it holds the potential for providing space to re-imagine our ecological relations.
Keywords: Canadian literature; Environmental Humanities; Ecocriticism; Agriculture; Georgics; Environment; Imperialism; Colonization; Labour